If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 6 = 46 + 3y Reorder the terms: 6 + 7y = 46 + 3y Solving 6 + 7y = 46 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 6 + 7y + -3y = 46 + 3y + -3y Combine like terms: 7y + -3y = 4y 6 + 4y = 46 + 3y + -3y Combine like terms: 3y + -3y = 0 6 + 4y = 46 + 0 6 + 4y = 46 Add '-6' to each side of the equation. 6 + -6 + 4y = 46 + -6 Combine like terms: 6 + -6 = 0 0 + 4y = 46 + -6 4y = 46 + -6 Combine like terms: 46 + -6 = 40 4y = 40 Divide each side by '4'. y = 10 Simplifying y = 10
| .45/x=2.05 | | 4e-16+5e=28 | | 40+5x=125 | | 10.358+2.416= | | 2k+7+8x=13 | | 10+x(x)=144 | | V+7=21 | | 8x^3=6x-8 | | 3x-2=4x+16 | | 4.5=-270h | | -8y+20=-4(y-8) | | 3x+2y+50=310 | | 2tan(x)sin(2x)=3 | | 3(2x+4)=78 | | 2x+6=128 | | 3c+10=16 | | .8k=19.2 | | N/6=5/15 | | x(5x+3)=2x^2-7x+8 | | -8+2n+14=-2n+4 | | -8+2n+14=-2a+4 | | 2x(3x-2x)=0 | | 5x^4-10x^3+3x^2=6x | | 3(2x-4)+3(x-1)=9 | | -9r-10=62 | | 3x+8y=6x-14y | | 14/10=n/35 | | 16x+8-4x=68 | | 7sin(x)+4=o | | -9r-10=63 | | h=-16t^2+114t+11 | | 149=16+3y |